IMPLEMENTASI MANAJEMEN DANA FILANTROPI WISATA RELIGI MAKAM GUS DUR (STUDI KASUS: LEMBAGA SOSIAL PESANTREN TEBUIRENG) - Primastri Ayu Damayanti; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The purpose of this study was to find out and analyze how the management of Gus Dur's grave religious tourist philanthropy was conducted by the Lembaga Sosial Pesantren Tebuireng in managing collected funds. This study uses qualitative methods with a case study strategy. The subject of this research is the Tebuireng Islamic Boarding School Social Institution. This research was conducted directly in the field to explore information relating to the management of philanthropic funds in Gus Dur's religious tourism tomb. Data collection was carried out by interviewing the board members of the Tebuireng Islamic Boarding School, direct observation and documentation. The results of this study are the Tebuireng Islamic Boarding School Institution in managing the collected funds applying four management functions, namely planning, organizing, mobilizing and controlling. In addition to implementing the four management functions, the Tebuireng Islamic Boarding School Social Institution also conducts a sharia management system in carrying out its organizational activities.Keywords: Management, philanthropic funds, Lembaga Sosial Pesantren TebuirengREFFERENCESDaft, R. L. (2006). MANAJEMEN. (R. Widyaningrum, Ed.) (6th ed.). Jakarta: Salemba Empat.Harahap, I., Nasution,  yenni samri juliati, Marliyah, & Syahriza, R. (2015). Hadis-Hadis Ekonomi (Pertama). Jakarta: PRENADAMEDIA GROUP.Kamil, S. (2016). Ekonomi Islam, Kelembagaan, dan Konteks Keindonesiaan. Jakarta: RajaGrafindo Persada.Linge, A. (2015). FILANTROPI ISLAM SEBAGAI INSTRUMEN KEADILAN EKONOMI. JURNAL PERSPEKTIF EKONOMI DARUSSALAM, 1(2502–6976), 155.Muttaqin, Y. (2018). Empat Motivasi Ziarah Kubur Menurut Syekh Nawawi Banten. Retrieved March 17, 2019, from http://www.nu.or.id/post/read/85822/empat-motivasi-ziarah-kubur-menurut-syekh-nawawi-bantenPendit, N. S. (1990). Ilmu Pariwisata: Sebuah Pengantar Perdana. Jakarta: Pradnya Paramita.Ruslan, & Nugroho, A. S. (2007). Ziarah Wali: Wisata Spiritual Sepanjang Masa. yogyakarta: pustaka timur.Sholihin, A. ifham. (2010). Buku Pintar Ekonomi Syariah. Jakarta: Gramedia Pustaka Utama.Sinn,  ahmad ibrahim abu. (2013). Manajemen Syariah. In manajemen berbasis syariah (p. 3). yogyakarta: Aswaja Pressindo.Sugiyono. (2011). Metode Penelitian Kuantitatif, Kualitatif dan R & D. Bandung: Penerbit Alfabeta.Syukur, A. (2002). Tuntunan Shalat Jenazah dan Ziarah Kubur. In Ziarah Wali :Wisata spiritual sepanjang masa (p. 6). yogyakarta: pustaka timur.Terry, G. R., & Rue, L. W. (2010). DASAR-DASAR MANAJEMEN (Empat). Jakarta: Bumi Aksara.Yin, R. K. (2015). Studi Kasus Desain & Metode. Jakarta: PT Raja Grafindo Persada.